Gated Cross-Modal Fusion Mechanism for Audio-Video-based Emotion Recognition - Kumar, Himanshu; Aruldoss, Martin (Engineering, Technology & Applied Science Research, 2025)
Due to its potential uses in security, surveillance, mental health monitoring, and human-computer interaction, artificial emotion recognition employing video and audio modalities has attracted a lot of attention. This study focuses on optimal cross-modal fusion techniques to enhance the precision and robustness of multimodal audio-video-based emotion recognition. Specifically, this study introduces a gated cross-modal fusion mechanism in audio-video-based emotion recognition, known as Compact Bilinear Gated Pooling (CBGP). The novelty of this work is that CBGP fusion is being applied to the emotion recognition task for the first time to integrate the extracted features and reduce the dimensionality of the audio and video modalities using 1DCNN and 3DCNN deep neural architectures, respectively. This novel approach was tested and verified on three benchmark datasets: CMU-MOSEI, RAVDESS, and IEMOCAP, each containing multimodal data representing a range of emotions, including happy, sad, fear, anger, neutral, and disgust. Experimental results show that CBGP consistently outperformed state-of-the-art fusion techniques, such as early fusion, late fusion, hybrid fusion, and others. CBGP extracts the relevant features, leading to higher accuracy and F1 scores due to its dynamic gating mechanism that selectively emphasizes relevant feature interactions. This study suggests that the integration of gating mechanisms within fusion processes is vital to improve emotion recognition. Future work will focus on extending these findings to real-time applications, exploring multitask learning frameworks, and enhancing the interpretability of multimodal emotion recognition systems.